Re-framing Photographic Archives: Archaeology and Colonial Cyprus - Stylianou-Lambert, Theopisti; Heraclidou, Antigone (My University, 2024)
This paper critically examines colonial-era photographic archives related to Cypriot archaeology maintained by museums and other collecting institutions in the UK and in Cyprus. It investigates how these archives can be decolonialised or re-framed. The institutions chosen as case studies are the British Museum, the Ashmolean Museum, the Institute of Archaeology at Oxford University, and the Bank of Cyprus Cultural Foundation. The examined archives were created in Cyprus by Western officials, explorers, and archaeologists: Falkland Warren, J.A.R. Munro, John Linton Myres, Luigi Palma di Cesnola, and Max and Magda Ohnefalsch-Richter. As a result, the photographs reflect the colonial attitudes of their creators and the power relations entrenched in archaeological work at the end of the 19th and beginning of the 20th centuries in Cyprus. The paper explores colonial marks, examines the case study institutions’ decolonisation strategies (if any), and suggests seven strategies for museums interested in reframing colonial-era photographic archives.
Keywords: Photographic archives; Cyprus; Museums; Archaeology